Obóz . niezależne pismo poświęcone problemom krajów ościennych, no. 9, 1984 - Ananicz, Andrzej; Maziarski, Wojciech; Korlak, Zbigniew; Jarocińska, Sławomira (s.n.], 1984)
Creation and circulation: From issue no. 19(1990) published legally